Efektifitas Citicoline dalam Meningkatkan Fungsi Kognitif: Analisis - Dermawan, Bagus; Ardhini, Rahmi; Puspita Wati, Arinta (Cermin Dunia Kedokteran, 2025)
Background: The incidence of cognitive impairment increased with age and with the presence of brain organic disorders. Citicoline allegedly improved cognitive function. This article to review the effectiveness of citicoline in improving cognitive function. Methods: A systematic search was conducted on 3 study databases: PubMed, Scopus, and EBSCO, to select studies according to the inclusion and exclusion criteria. Selected articles were then critically reviewed and further analyzed. Results: In the final analysis, 2 articles were to be reviewed. In 1 study in a healthy population, citicoline 500 mg/day for 3 months showed improvement in cognitive function, especially in memory domain, in 1 other study on post-ischemic stroke population, citicoline 1,000 mg/day for 12 months showed improvement in cognitive function especially in the attention, executive, and temporal orientation domains. Conclusion: Citicoline can improve cognitive function in both healthy population and post-ischemic stroke population.